Estimation of Germanicol by Validated HPTLC Densitometric Method in Leaves of Different Species of Genus Ficus - Siddiqui, N.A.; Basudan, O.A.; Alajmi, M.F.; Al-Rehaily, A.J.; Alqasoumi, S.I.; Abdel-Kader, M.S.; Alam, P.; Donia, A.R.M.; Alam, P. (Asian Journal of Chemistry, 2014)
A simple and sensitive HPTLC method was developed for estimation of germanicol in the leaves of five different species of genus Ficus (Ficus carica, Ficus nitida, Ficus ingens, Ficus palmata and Ficus vasta) grown in Kingdom of Saudi Arabia. The chromatography was performed on glass-backed silica gel 60 F254 HPTLC plates with solvents hexane: chloroform (55:45, v/v) as mobile phase. After the development of HPTLC plate it was derivatized with p-anisaldehyde reagent to give well resolved and compact spot of germanicol. The developed method was found to give a compact spot for germanicol (Rf = 0.39 ± 0.01) at 525 nm. Germanicol was found to be present in four species i.e., F. carica (0.21%, w/w), F. nitida (0.22%, w/w), F. palmata (1.06%, w/w) and F. vasta (0.27%, w/w) while it was absent in the F. final. The proposed method can be used in study of degradation kinetics of germenicol and its determination in plasma.